International cooperation on climate change adaptation from an economic perspective - Kelly C. de Bruin; Rob B. Dellink; Richard S.J. Tol (The Economic and Social Research Institute (ESRI), 2009)
This paper investigates the economic incentives of countries to cooperate on international adaptation financing. Adaptation is generally implicitly incorporated in the climate change damage functions as used in Integrated Assessment Models. We replace the implicit decision on adaptation with explicit adaptation in a multi-regional setting by using an adjusted RICE model. We show that making adaptation explicit will not affect the optimal mitigation path when adaptation is set at its optimal level. Sub-optimal adaptation will, however, change the optimal mitigation path. Furthermore this paper studies for different forms of cooperation what effects international adaptation transfers will have on (i) domestic adaptation and (ii) the optimal mitigation path. Adaptation transfers will fully crowd out domestic adaptation in a first best setting. Transfers will decrease overall mitigation in our numerical simulations. An analytical framework is used to analyse the most important mechanisms and a numerical model is used to assess the magnitude of effects.
Keywords: 330; climate change; adaptation funding; Integrated Assessment Modeling; Internationale Umweltpolitik; Kooperation; Umweltschutzinvestition; Wirkungsanalyse; Theorie